Evidence of cortical thickness increases in bilateral auditory brain structures following piano learning in older adults. Issue 1 (15th March 2022) - Worschech, Florian; Altenmüller, Eckart; Jünemann, Kristin; Sinke, Christopher; Krüger, Tillmann H. C.; Scholz, Daniel S.; Müller, Cécile A. H.; Kliegel, Matthias; James, Clara E.; Marie, Damien
Abstract: Morphological differences in the auditory brain of musicians compared to nonmusicians are often associated with life‐long musical activity. Cross‐sectional studies, however, do not allow for any causal inferences, and most experimental studies testing music‐driven adaptations investigated children. Although the importance of the age at which musical training begins is widely recognized to impact neuroplasticity, there have been few longitudinal studies examining music‐related changes in the brains of older adults. Using magnetic resonance imaging, we measured cortical thickness (CT) of 12 auditory‐related regions of interest before and after 6 months of musical instruction in 134 healthy, right‐handed, normal‐hearing, musically‐naive older adults (64–76 years old). Prior to the study, all participants were randomly assigned to either piano training or to a musical culture/music listening group. In five regions—left Heschl's gyrus, left planum polare, bilateral superior temporal sulcus, and right Heschl's sulcus—we found an increase in CT in the piano training group compared with the musical culture group. Furthermore, CT of the right Heschl's gyrus could be identified as a morphological substrate supporting speech in noise perception. The results support the conclusion that playing an instrument is an effective stimulator for cortical plasticity, even in older adults. Abstract : Using magnetic resonance imaging (MRI), we measured cortical thickness of 12 auditory‐related regions of interest before and after six months of musical instruction in 134 healthy, right‐handed, normal‐hearing, musically naive older adults. The results support the conclusion that playing an instrument is an effective stimulator for cortical plasticity, even in older adults.